Respostas

2014-01-28T20:55:05-02:00
Δ = b² -4ac
Δ = 0² -4 *(-3) * 108
Δ = 0 + 1296
Δ = 1296
x' = (-b + √∆)/ 2a
(-0 + 36)/2 * (-3)
(0 + 36)/-6
36/-6
-6
x'' = (-b - √∆)/ 2a
(-0 - 36)/2 * (-3)
(0 - 36)/-6
-36/-6
6



x^2 -4x+3=0

Δ = b² -4ac
Δ= (-4)² -4 *1 * 3
Δ = 16 -12
Δ = 4
x' = (-b + √∆)/ 2a
(-(-4) + 2)/2 * 1
(4 + 2)/2
6/2
3
x'' = (-b - √∆)/ 2a
(-(-4) - 2)/2 * 1
(4 - 2)/2
2/2
1

1 5 1
2014-01-28T22:45:18-02:00
Temos aqui duas equações de segundo grau:

-3x² + 108 = 0 
x² - 4x + 3 = 0

Vamos às resoluções das mesmas:

-3x² + 108 = 0 
a= -3
b= 0
c= 108
Δ= b²-4.a.c
Δ= 0²-4.(-3).108
Δ= 0+1296
Δ= 1296
Δ= -b±√Δ
        2.a
Δ= 0±36
      2.(-3)
x'= 0+36 
      -6
x'=_ 36
         6
x'= -6
x''= 0-36
        -6
x''= -36
      -6
x''= 6

S= {-6,6}

x² - 4x + 3 = 0
a= 1
b= -4
c=3
Δ= b²-4.a.c
Δ= (-4)²-4.1.3
Δ= 16-12
Δ=4
Δ= -b ±√Δ
         2.a
Δ= 4±2
      2.1
x'= 4+2
       2
x'= 6
      2
x'= 3
x''= 4-2
        2
x''=
     2
x''= 1

S= {1,3}